ANALISIS KINERJA KEUANGAN PT KIMIA FARMA TBK MENGGUNAKAN METODE ECONOMIC VALUE ADDED PERIODE 2016-2019 - Abdul Sumarlin (AkMen JURNAL ILMIAH, 2020)
PT Kimia Farma Tbk's NOPAT (Net Operating After Tax) value deteriorated from 2017 to 2019. NOPAT is an operating profit after deducting tax which is a return on the total invested capital. So that NOPAT is the best indicator in assessing cash-generating posts, and if a company has a low NOPAT value, the company's EVA (Economic Value Added) value will also be low and vice versa. This study aims to determine the financial performance of the pharmaceutical company PT Kimia Farma Tbk (Persero) which is listed on the Indonesia Stock Exchange (BEI) with the EVA approach from 2016-2019. This type of research used descriptive quantitative. The data analysis method used is documentation by applying the Economic Value Added (EVA) formula to the financial statements of PT Kimia Farma Tbk during the research period from 2016 to 2019. The results show the calculation of the EVA of PT Kimia Farma Tbk for the period 2016 and 2017 has a positive value or EVA> 0, which means that PT Kimia Farma Tbk is able to create economic added value, because the net profit earned by the company is greater when compared to the cost of capital used. However, in the 2018 and 2019 periods it has a negative value or EVA <0, which means that PT Kimia Farma Tbk is unable to create added economic value, because the company's total capital is greater than the operating profit after tax it receives, so it can be concluded that in 2018-2019 the company's performance not good. As input for PT Kimia Farma Tbk, it is better if you minimize the use of your own capital so that taxes borne by the company can be reduced and you can balance your own capital with loan capital so that the average WACC will get stable results.